Principles of meiotic chromosome assembly revealed in S. cerevisiae - Schalbetter, Stephanie A.; Fudenberg, Geoffrey; Baxter, Jonathan; Pollard, Katherine S.; Neale, Matthew J. (Nature communications, 2019)
During meiotic prophase, chromosomes organise into a series of chromatin loops emanating from a proteinaceous axis, but the mechanisms of assembly remain unclear. Here we use Saccharomyces cerevisiae to explore how this elaborate three-dimensional chromosome organisation is linked to genomic sequence. As cells enter meiosis, we observe that strong cohesin-dependent grid-like Hi-C interaction patterns emerge, reminiscent of mammalian interphase organisation, but with distinct regulation. Meiotic patterns agree with simulations of loop extrusion with growth limited by barriers, in which a heterogeneous population of expanding loops develop along the chromosome. Importantly, CTCF, the factor that imposes similar features in mammalian interphase, is absent in S. cerevisiae , suggesting alternative mechanisms of barrier formation. While grid-like interactions emerge independently of meiotic chromosome synapsis, synapsis itself generates additional compaction that matures differentially according to telomere proximity and chromosome size. Collectively, our results elucidate fundamental principles of chromosome assembly and demonstrate the essential role of cohesin within this evolutionarily conserved process. During meiotic prophase chromosomes organise into a series of chromatin loops, but the mechanisms of assembly remain unclear. Here the authors use Saccharomyces cerevisiae to elucidate how this elaborate three-dimensional chromosome organisation is linked to genomic sequence, and demonstrate an essential role for cohesin during this process.